Understanding Milk Consumption Habits Among College Students in Order to Redesign Outreach - Stacey F. Stearns; Adam N. Rabinowitz ([TEST] Journal of Extension, 2021)
College students consume less dairy milk than in the past. Increased competition in the beverage aisle influences their choices. However, much of the population is not meeting the recommended intake guidelines for calcium. A survey of undergraduate college students with university dining plans focused on milk consumption habits, beverage choices, and student attitudes toward healthful foods and nutrition. Results are guiding Extension program educational outreach campaigns to college students. By focusing on the healthful and nutritional benefits of milk, Extension educators could increase consumption among college age consumers, and their long-term healthful outcomes.
Keywords: dairy; milk; college students; beverage preferences; nutrition